2019
DOI: 10.3389/fpls.2019.01118
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis MDN1 Is Involved in the Establishment of a Normal Seed Proteome and Seed Germination

Abstract: Seed germination and formation are the beginning and ending, respectively, of a plant life cycle. These two processes are under fine regulation by the internal genetic information. Previously, we demonstrated that Arabidopsis MIDASIN 1 (MDN1) is required for ribosome biogenesis, and its dysfunction leads to pleiotropic developmental phenotypes, including impaired embryogenesis and slow seed germination. In this study, we further found that the weak mutant of MDN1, mdn1-1, exhibits an increased seed size phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Within the numerous available seed proteomic reports (Narula et al, 2016), studies directly aiming at the identification of protein involved in seed longevity/viability present in dry seeds unveiled 309 differentially accumulated proteins in GERMINATION ABILITY AFTER STORAGE (GAAS) lines (Nguyen et al, 2015), 320 in mdn1-1 (Li et al, 2019), and 442 in vps29 mutants (Durand et al, 2019). The study using GAAS lines exploited natural variation in seed storability and proposed that the highly abundant Cruciferin storage proteins (CRA, CRB and CRC) act as a ROS buffering system (Nguyen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the numerous available seed proteomic reports (Narula et al, 2016), studies directly aiming at the identification of protein involved in seed longevity/viability present in dry seeds unveiled 309 differentially accumulated proteins in GERMINATION ABILITY AFTER STORAGE (GAAS) lines (Nguyen et al, 2015), 320 in mdn1-1 (Li et al, 2019), and 442 in vps29 mutants (Durand et al, 2019). The study using GAAS lines exploited natural variation in seed storability and proposed that the highly abundant Cruciferin storage proteins (CRA, CRB and CRC) act as a ROS buffering system (Nguyen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Proteins over-accumulated exclusively in the unusual combination of extreme ABA resistance and seed storability (Cluster IV) include a GIBBERELLIN METHYLTRANSFERASE, which is normally expressed during seed maturation, leading to inactivation of GA (Varbanova et al, 2007), MIDASIN1 (MDN1) previously shown to be required for a proper shaping of the seed maturation proteome (Li et al, 2019), and a Pumilio RNA binding protein (APUM24), for which loss of function leads to aborted seeds (Maekawa et al, 2017). These seeds also over-accumulate a beta-glucoside that releases ABA from a conjugated form (AtBG1) (Lee et al, 2006) and is up-regulated by ABA-deficiency (Chauffour et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins regulate catabolism [44], energy metabolism [45], anabolism, and defense reactions [46]. A previous study showed that rate of seed germination in Arabidopsis midasin1-1 (mdn1-1) was decreased by increasing the expression levels of SEED STORAGE ALBUMIN (SESA)1/3/4/5, EMBRYO SAC DEVELOPMENT ARREST4, and ABI5 compared with wild type (Col-0) [47]. In the present study, 17 proteins were identi ed in the Phellodendron chinense Schneid seeds during germination under normal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The flc-3 (104 bp deletion in the first exon), flk-4 (Salk_112850), fve-4 (TGG to TGA mutation in the 6th exon), co (SAIL_24_H04), ft-10 (GABI_290E08), and clf-28 (SALK_139371) mutants were kindly provided by prof. Scott Michaels (Indiana University Bloomington). The double mutant of mdn1-1 abi5 had been described in our previous study [ 51 ]. Seedlings and plants were grown under 16 h light/8 h dark (LD, long day) or 8 h light/16 h dark (SD, short day) conditions at 21 °C.…”
Section: Methodsmentioning
confidence: 99%